Measurement of cervical length using transvaginal sonography for prediction of preterm labour - Raval, Bina M.; Sisodiya, Viditsinh P.; Yadava, Pushpa A.; Mehta, Shital T.; Patel, Sagar R.; Dadhania, Bintu H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Preterm labour and delivery cause major health burden to the society due to high perinatal morbidities and mortality and long-term health implications and also affects maternal. An effective and objective way for predicting preterm delivery is measurement of cervical length by transvaginal sonography as it allows better quality and accurate visualization of uterine cervix. Cervical length (<25 mm) is good and accurate cervical biometry for prediction of preterm birth. The objective of this study was to measure cervical length by transvaginal sonography for predicting preterm labour and fetal outcome. Methods: This prospective observational study was conducted in department of obstetrics and gynaecology, at SVPIMSR hospital, Ahmedabad from July 2018 to December 2019 in 150 antenatal women to assess cervical changes (cervical length, dilatation of internal OS, funnelling etc.) between 16 to 24 weeks of gestation and these cases followed till delivery and results were analysed. Results:150 antenatal women who fulfilled the selection criteria were studied using transvaginal ultrasound between 16-24 weeks of gestation, out of them 36 (24%) women delivered preterm babies. The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) recorded in this study were 80.5%, 94.73%, 82.85% and 93.91% respectively. Conclusion: Transvaginal sonography is the most useful and better, safe, accurate, most effective, less expensive, objective and acceptable technique for assessing cervical length in all antenatal women and predicting the preterm labour when assessed between 16 -24 weeks of gestational age.